2020
DOI: 10.1371/journal.pone.0243943
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition and decay of IgM and IgG responses to merozoite antigens after Plasmodium falciparum malaria in Ghanaian children

Abstract: Developing a vaccine against Plasmodium falciparum malaria has been challenging, primarily due to high levels of antigen polymorphism and a complex parasite lifecycle. Immunization with the P. falciparum merozoite antigens PfMSRP5, PfSERA9, PfRAMA, PfCyRPA and PfRH5 has been shown to give rise to growth inhibitory and synergistic antisera. Therefore, these five merozoite proteins are considered to be promising candidates for a second-generation multivalent malaria vaccine. Nevertheless, little is known about I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 65 publications
1
9
2
Order By: Relevance
“…There was also some boosting to non-blood stage antigens, with increased OPA antibodies to both CSP and Pfs230 during infection. IgM antibodies were not increased to any antigens in currently infected children, in contrast with previous findings by ourselves and others (Boyle et al, 2019;Walker et al, 2020).…”
Section: Antibody Responses Are Higher In Children With Current Infec...contrasting
confidence: 68%
“…There was also some boosting to non-blood stage antigens, with increased OPA antibodies to both CSP and Pfs230 during infection. IgM antibodies were not increased to any antigens in currently infected children, in contrast with previous findings by ourselves and others (Boyle et al, 2019;Walker et al, 2020).…”
Section: Antibody Responses Are Higher In Children With Current Infec...contrasting
confidence: 68%
“…In contrast, we found that hyper-immune adults from PNG (used as the positive control pool) had similar levels of IgG1 and IgG3 to multiple P. vivax proteins, and that the level of IgG3 was higher compared to that of the Thai symptomatic patients to most proteins (Figure S3). Naturally acquired antigen-specific IgM responses are longer-lived than total IgG following symptomatic P. vivax infections Whilst IgM responses are traditionally thought to be transient following infections, more recent evidence has suggested they can be long-lived or follow a similar kinetic to IgG, at least in the context of malaria [44,45], though this is likely dependent on the antigen assessed and transmission setting [46]. We first assessed IgM immunogenicity at 1-week post-infection in the symptomatic cohort and classified 15 antigens as IgMpositive (more than 2 SD above baseline), including both IgG-immunogenic (n=8) and non-IgG-immunogenic (n=7) antigens (Figure S4).…”
Section: Naturally Acquired Total Igg Kinetics Are Antigen-specific and Dominated By Subclass Igg1 Following Symptomatic P Vivax Infectiomentioning
confidence: 99%
“…PfCyRPA is a 43 kDa protein with only one single-nucleotide polymorphism (SNP), R339S, above 5% prevalence (14). The protein is fundamental for erythrocyte invasion as conditional knockdown causes the loss of invasion activity (11,15) and the protein has low sero-reactivity from natural exposure (16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%